Transition from school-based training in VET. Issue 1 (9th January 2017) - Dæhlen, Marianne
Abstract : Purpose: This paper assesses the drop-out rate among disadvantaged students within vocational education and training. The purpose of this paper is to examine the probability of dropping out after school-based training for child welfare clients – a particularly disadvantaged group of youth. Child welfare clients' drop-out rate is compared with students from a representative sample of their peers. Design/methodology/approach: Average marginal effects were calculated from multinomial logistic regression models. Data were from public registries ( n =10, 535). Findings: The results show that differences in observed characteristics cannot explain differences in drop-out rates between child welfare clients and the majority peers. It is argued that this drop-out rate is likely a result of employers favoring apprenticeship applicants who are similar to them or that child welfare clients lack networks, which previous research has identified as crucial in finding an apprenticeship. Practical implications: The results suggest a need for action targeting disadvantaged youths in the transition that follows school-based training. Originality/value: The paper adds to the very scarce literature on transition from school-based learning to apprenticeships.